Use of criterion of midfrequency of emissions in the process of environmental control - Любимова, Нина Александровна (Eastern-European Journal of Enterprise Technologies, 2014)
In this paper, it is proposed to use the midfrequency of the emissions of the controlled parameters as a criterion for environmental control of the gaseous emissions and liquid discharges of the energy-intensive enterprises. A mathematical model of the midfrequency of the emissions of the controlled pollution process as the sum of the amplitude and phase components is considered. Analytical expressions of these components are obtained. Graphical interpretations of the components for optimizing the control and preventive limits, and intervals for a minimum criterion of the midfrequency of the emissions are analyzed. Experimental use of the model of the midfrequency of the emissions during the active control of the concentrations of sulfur oxide in the power plant emissions is considered. The obtained results allow adjusting the control and preventive limits and optimally organizing them during planning. Using this model increases the reliability, sensitivity of control to prevent the violations of natural resource management.